On a Nevanlinna type result for solutions of nonautonomous equations y′=a( t) F 1( x,y), x′=b( t)F 2( x,y ) - Barseghyan, K. G.; Barsegian, G. A. (Complex variables, theory & application, 2005)
Oscillation problems (investigation of zeros) were widely studied for solutions of ordinary differential equation (ODE). In this article, we transfer oscillation problems to the case of solutions of nonautonomous system of equations . By analogy with the theory of oscillation for one ODE, we consider number n(t 1 ,t 2 ,0) of zeros τ i in (t 1 ,t 2 ) of the solutions, that is the number of those points τ i , where x(τ i ) =0 and y(τ i )=0. It turns out that the above bounds for n(t 1 ,t 2 ,0) can be given in terms of a( t) , b( t) , F 1 , F 2 , t 1 and t 2 . Also by analogy with the concept of a-points in the complex analysis, we consider values a:=(a′,a″) in the ( x, y )-plane and define a-points of the solutions as those points τ i , where and . Denoting by n(t 1 ,t 2 , a) the number of a-points in (t 1 ,t 2 ) of the solutions we give above bounds for the sum , where a 1 ,a 2 ,...,a q is a given totality of pairwise different points. Thus we obtain for the solutions of the above equation an analog of the second fundamental theorem in the Nevanlinna value distribution theory; the last one also considers a similar sum for the number of a-points of meromorphic functions. As an immediate application we obtain below bounds for the periods of periodic solutions.